High-dose inhaled terbutaline in the management of chronic severe asthma: comparison of wet nebulisation and tube-spacer delivery. Issue 4 (April 1982) - Prior, J G; Nowell, R V; Cochrane, G M
Abstract : Eight patients with chronic severe asthma, poorly controlled by conventional doses of inhaled bronchodilator, were treated with high-dose inhaled terbutaline (4 mg four times daily), via either wet nebulisation of terbutaline respirator solution, or by tube-spacer aerosol, using cannisters delivering 1 mg terbutaline per metered dose. All patients improved objectively and subjectively on these higher dosage regimens during both day and night. A trial of high-dose inhaled beta2 sympathomimetic therapy should be considered in any patient with chronic severe asthma who fails to obtain benefit from standard doses of inhaled bronchodilator.